An auxiliary system for rehabilitation training. Issue 1 (May 2021) - Liu, Xuehua; Lin, Zhenkun; Lin, Zhencheng
Abstract: In this paper, aiming at the problem of sports injury in squatting, the development of squatting training assistant system based on MPU9250 is proposed and designed. The system uses embedded technology, through the cloud architecture of recurrent neural network to analyze data, realize the monitoring of squat training, return the results to the mobile APP end, realize the correction and guidance of each action, and display the user's rehabilitation in real time. Through the system test, the results show that the system has the characteristics of stable performance, accurate detection, convenient and portable.